The Teachers' Role in Developing Students Social Skills in Social Studies Subject at Vocational High School - Mujiatin Setyana (Universitas Negeri Malang, 2015)
Peran Guru dalam Mengembangkan Keterampilan Sosial Siswa Mata Pelajaran IPS di SMK Abstract: This study aims to explain: 1) teachers' understanding of social skills in social studies at SMK; 2) the role of social studies teachers in vocational schools were in designing learning social studies students develop social skills; 3) the implementation of learning undertaken by teachers in vocational IPS that can develop social skills; 4) assessment conducted in vocational teachers in so-cial studies is to develop social skills. The study used a qualitative descriptive research design with case study. The techniques used were interviews, observation and documentationThe results showed: teachers' understanding of the lack of social skills; RPP has not led to the development of social skills, cooperative learning models used in the learning is not maximized; assessment conducted by a social studies teacher tends cognitive, while the affective and psychomotor assessment ignored. Key Words: roles of teachers, the learning of social studies, social skills   Abstrak: Penelitian ini bertujuan untuk menjelaskan 1) pemahaman guru tentang keterampilan sosial pada mata pelajaran IPS di SMK; 2) peran guru-guru IPS di SMK dalam merancang pembelajaran IPS yang mengembangkan keterampilan sosial siswa; 3) pelaksanaan pembelajaran yang dilakukan oleh guru-guru IPS di SMK yang dapat mengembangkan keterampilan sosial; 4) penilaian yang dilakukan guru-guru di SMK pada mata pelajaran IPS yang mengembangkan keterampilan sosial. Penelitian menggunakan rancangan penelitian deskriptif kualitatif dengan studi kasus. Teknik yang digunakan adalah wawancara, observasi dan dokumentasi. Hasil penelitian menunjukkan: pemahaman guru tentang keterampilan sosial kurang; RPP belum mengarah pada pengembangan keterampilan sosial, model cooperative learning yang digunakan dalam pembelajaran belum maksimal; penilaian yang dilakukan oleh guru IPS cenderung kognitif, sedangkan penilaian afektif dan psikomotor diabaikan. Kata kunci: peran guru, pembelajaran IPS, keterampilan sosial